Taming the elephant : politics, government, and law in pioneer California - Burns, John F.; Orsi, Richard J. (California history sesquicentennial series, 2003)
The final of four volumes in the 'California History Sesquicentennial Series', this text compiles original essays which treat the consequential role of post-Gold Rush California government, politics and law in the building of a dynamic state with lasting impact to the present day.